Pendidikan Tinggi Islam dan Pengembangan Entrepreneuer Skill - Muhammad Muhammad (Dinamika Ilmu, 2009)
Islamic education has three related foundations. One of the intended foundations is education and teaching. Without leaving aside other two foundations (research and dedication to the society), education is the important element that becomes the instrument of potential development of human resources that have competitive superiority. Two kinds of these superiorities (added by collaborative and spiritual superiority) become “condition sine qua non” that has to be developed by Islamic education world, so that its existence will not be the “ivory tower”. The knowledge expansion from normative way to the development of business skill which stands on religious values as “added value” that becomes a must in the middle of crowded global economic. The objectives of this article are to explain the basic economic concept which is built on the foundation and religious value (Read: Islamic Economy), entrepreneurship character building and the role of Islamic University.